RNA-Seq Comparison of Larval and Adult Malpighian Tubules of the Yellow Fever Mosquito Aedes aegypti Reveals Life Stage-Specific Changes in Renal Function - Li, Yiyi; Piermarini, Peter M.; Esquivel, Carlos J.; Drumm, Hannah E.; Schilkey, Faye D.; Hansen, Immo A. (Frontiers in Physiology, 2017)
Introduction - The life history of Aedes aegypti presents diverse challenges to its diuretic system. During the larval and pupal life stages mosquitoes are aquatic. With the emergence of the adult they become terrestrial. This shifts the organism within minutes from an aquatic environment to a terrestrial environment where dehydration has to be avoided. In addition, female mosquitoes take large blood meals, which present an entirely new set of challenges to salt and water homeostasis. Methods - To determine differences in gene expression associated with these different life stages, we performed an RNA-seq analysis of the main diuretic tissue in A. aegypti, the Malpighian tubules. We compared transcript abundance in 4th instar larvae to that of adult females and analyzed the data with a focus on transcripts that encode proteins potentially involved in diuresis, like water and solute channels as well as ion transporters. We compared our results against the model of potassium- and sodium chloride excretion in the Malpighian tubules proposed by Hine et al (2014), which involves at least 8 ion transporters and a proton-pump. Results - We found 3,421 of a total number of 17,478 (19.6%) unique transcripts with a P-value < 0.05 and at least a 2.5 fold change in expression levels between the two groups. We identified two novel transporter genes that are highly expressed in the adult Malpighian tubules, which have not previously been part of the transport model in this species and may play important roles in diuresis. We also identified candidates for hypothesized sodium and chloride channels. Detoxification genes were generally expressed higher in larvae than in adults. Significance - This study represents the first comparison of Malpighian tubule transcriptomes between larval and adult A. aegypti mosquitoes, highlighting key differences in their renal systems that arise as they transform from an aquatic filter-feeding larval stage to a terrestrial, blood-feeding adult stage.